Mediating pathways between parental socio-economic position and allostatic load in mid-life: Findings from the 1958 British birth cohort - Barboza Solís, Cristina (2016)
Understanding how human environments affect our health by “getting under the skin” and penetrating the cells, organs and physiological systems of our bodies is a key tenet in public health research. Here, we examine the idea that early life socioeconomic position (SEP) can be biologically embodied, potentially leading to the production of health inequalities across population groups. Allostatic load (AL), a composite measure of overall physiological wear-and-tear, could allow for a better understanding of the potential biological pathways playing a role in the construction of the social gradient in adult health. We investigate the factors mediating the link between two components of parental SEP, maternal education (ME) and parental occupation (PO), and AL at 44 years. Data was used from 7573 members of the 1958 British birth cohort follow-up to age 44. AL was constructed using 14 biomarkers representing four physiological systems. We assessed the contribution of financial/materialist, psychological/psychosocial, educational, and health behaviors/BMI pathways over the life course, in mediating the associations between ME, PO and AL. ME and PO were mediated by three pathways: educational, material/financial, and health behaviors, for both men and women. A better understanding of embodiment processes leading to disease development may contribute to developing adapted public policies aiming to reduce health inequalities.